Phase change temperature regulating fiber and its application in thermal insulation fabric

CN122543196BActive Publication Date: 2026-10-30SHANGHAI LIANGFENG LEADING TECH DEV CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611039135.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-30
Estimated Expiration
2046-07-14

AI Technical Summary

Technical Problem

但这类纳米填料表面能高,在聚合物基体中极易团聚,与基体材料的相容性差

Benefits of technology

[0038]1.本发明采用异氰酸酯单体将马来酸酐共聚物SEBS-g-MA与纳米导热填料共价连接,形成SEBS-UPy-填料桥联结构。该结构将填料牢固锚定在弹性体基体上,避免了物理共混中易出现的填料团聚和界面脱粘问题,同时UPy单元可作为后续超分子网络的结合节点,实现填料分散、界面增强与超分子功能的一体化构建。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122543196B_ABST
    Figure CN122543196B_ABST
Patent Text Reader

Abstract

The application discloses a phase change temperature regulating fiber and application thereof in thermal-keeping fabrics, and belongs to the technical field of intelligent textile materials. The fiber takes double-end hydroxyl polyethylene glycol as a phase change base material, constructs a dynamic covalent network through aromatic boric acid, realizes chemical bridging of a maleic anhydride copolymer SEBS-g-MA and nano heat-conducting fillers by using an isocyanate monomer containing a UPy group, and forms a three-dimensional reversible supramolecular network in cooperation with a supramolecular crosslinking agent. The application solves the problems of traditional phase change fibers, such as easy leakage, latent heat attenuation, poor spinnability and the like, the prepared fiber has high fiber phase change enthalpy, excellent mechanical properties, thermal cycle stability, fast heat-conducting response, can be directly melt-spun and used in thermal-keeping fabrics, and has a good application prospect in the field of intelligent temperature regulating textiles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of intelligent textile materials technology, and in particular to a phase change temperature-regulating fiber and its application in thermal insulation fabrics. Background Technology

[0002] Phase change thermally modulating fibers are a type of smart fiber that can absorb or release latent heat by undergoing a solid-liquid phase transition when the external temperature changes. These fibers can effectively buffer the heat flow between the human body and the external environment, providing wearers with a continuous thermal comfort experience, and have broad application prospects in fields such as smart clothing, outdoor sports equipment, and home textiles.

[0003] Current technologies for preparing phase change temperature-regulating fibers mainly revolve around microencapsulation, core-sheath structure filling, and physical adsorption. Microencapsulation, by encapsulating the phase change material (PCM) within a polymer shell, effectively mitigates leakage during fiber processing and use. However, microcapsule walls are often rigid polymers, which are prone to rupture under the high temperatures and shear conditions of melt spinning, leading to core leakage and significant loss of fiber enthalpy; furthermore, the introduction of microcapsules reduces the fiber's thermal conductivity. Core-sheath structure filling places the PCM in the fiber core layer and encapsulates it in the sheath, but the lack of chemical bonding between the sheath and core results in limited interfacial strength, leaving the PCM at risk of migration and leakage along the fiber axis after long-term use. Physical adsorption relies on porous carriers to adsorb the PCM; however, the PCM within the pores gradually precipitates during repeated phase changes, and the carriers have poor mechanical properties, making it difficult to meet the fiber strength requirements of textile processing and daily use.

[0004] To address the leakage issues caused by physical encapsulation, existing technologies have attempted to anchor phase change materials such as polyethylene glycol (PEG) within a polymer network using chemical cross-linking. However, traditional high-density static covalent cross-linked networks severely restrict the movement of PEG molecular chains, leading to a sharp decrease in PEG crystallinity and a significant reduction in latent heat of phase change. Simultaneously, the highly cross-linked system exhibits extremely high melt viscosity, losing its thermoplastic processing properties and making it difficult to mold using melt spinning processes.

[0005] Furthermore, to improve the overall performance of fibers, some studies have attempted to add high thermal conductivity fillers, such as carbon nanotubes and boron nitride nanosheets, to the system to enhance the thermal response rate of phase change materials. However, these nanofillers have high surface energy and are prone to agglomeration in the polymer matrix, exhibiting poor compatibility with the matrix material. Currently used physical blending or simple surface modification methods are insufficient to maintain uniform dispersion of fillers under the high shear forces of melt spinning, and there is a lack of strong chemical bonds between the fillers and the matrix. Filler agglomeration not only weakens the thermal conductivity enhancement effect but also becomes a stress concentration point, leading to a significant decrease in the mechanical properties of the fiber.

[0006] Therefore, developing a phase change temperature-regulating fiber preparation technology that can simultaneously solve the contradiction between leakage and latent heat decay of phase change materials, endow the system with excellent thermoplastic processability, and achieve stable chemical dispersion of nanofillers still has important research significance and application value. Summary of the Invention

[0007] The purpose of this invention is to address the shortcomings of existing technologies by proposing a phase change temperature-regulating fiber and its application in thermal insulation fabrics.

[0008] To achieve the above objectives, the present invention adopts the following technical solution:

[0009] A phase change temperature-regulating fiber, comprising the following components in parts by weight:

[0010] 50-80 parts of hydroxyl-terminated polyethylene glycol, 0.5-5 parts of aromatic boric acid compounds, 1-5 parts of supramolecular crosslinking agent, 10-40 parts of maleic anhydride copolymer SEBS-g-MA, 0.1-5 parts of nano-thermal conductive filler, 0.2-1.0 parts of composite antioxidant, and 0.5-3 parts of isocyanate monomer;

[0011] The isocyanate monomer is an UPy intermediate containing a monoisocyanate group; the maleic anhydride copolymer SEBS-g-MA and the nano-thermal conductive filler are bridged by the isocyanate monomer.

[0012] This innovative approach introduces a hybrid bridging mechanism of "chemical anchoring-physical entanglement." The isocyanate monomer acts as a "molecular bridge," with its -NCO groups at both ends forming thermodynamically stable urethane bonds (chemical anchoring) with the hydroxyl groups generated from the in-situ ring-opening of SEBS-g-MA via maleic anhydride and the hydroxyl groups on the filler surface. Meanwhile, the UPy groups in the middle of the molecule extend outwards as "flexible hubs." The UPy groups exhibit a strong tendency for self-complementary dimerization through quadruple hydrogen bonds. This dimerization exhibits covalent bond strength at room temperature but is dynamically reversible under external forces or high temperatures. Through this design, the originally incompatible rigid nanofiller and elastomer matrix are not only forcibly brought closer by covalent bonds but also form a dense physical entanglement network through the UPy hubs, completely eliminating interfacial stress concentration points.

[0013] Preferably, in the bridging structure, the isocyanate groups of the isocyanate monomer form urethane bonds with the hydroxyl groups generated in situ from the ring-opening of the maleic anhydride copolymer SEBS-g-MA chain and the hydroxyl groups on the surface of the nano-thermal conductive filler, with the UPy group as the bridging node.

[0014] Preferably, the preparation method of the isocyanate monomer and supramolecular crosslinking agent includes the following steps:

[0015] (1) Preparation of isocyanate monomer: Under nitrogen protection, isophorone diisocyanate and anhydrous DMF are added to the reactor, along with dibutyltin dilaurate (DBTDL) and BHT polymerization inhibitor accounting for 0.1% of the mass of isophorone diisocyanate; 2-amino-4-hydroxy-6-methylpyrimidine is dispersed in anhydrous DMF and slowly added dropwise to the reaction solution at 0-5℃ in an ice bath; after the addition is complete, the reaction is maintained at 0-10℃ for 1-2 h, and then the temperature is raised to 40-50℃ for 4-6 h. After the reaction is completed, the solvent is removed to obtain the isocyanate monomer;

[0016] Due to strong hydrogen bonding, the UPy group is prone to uncontrolled aggregation or gelation in solution. This step precisely controls the difference in reactivity between the primary and secondary isocyanate groups of isophorone diisocyanate (IPDI) at low temperature, causing the secondary -NCO to preferentially react with the pyrimidine amino group to form a urea bond, while retaining the primary -NCO. This transforms the highly polar UPy into a monoisocyanate-terminated "reactive monomer," essentially giving UPy a "targeted gripper." The weakening effect of the steric hindrance in the IPDI framework ensures that this structure remains stable before subsequent melt processing, preventing premature association and ensuring that the -NCO group can accurately and efficiently attach to the hydroxyl groups on the matrix and filler surfaces during the spinning stage.

[0017]

[0018] (2) Preparation of supramolecular crosslinking agent: Dissolve the isocyanate monomer obtained in step (1) in anhydrous DMF and cool to 10-15℃. Dissolve the rigid diamine monomer in anhydrous DMF and control the mass percentage concentration of the rigid diamine monomer to be 5-10%. Add it slowly dropwise to the reaction system under vigorous stirring for 2-4 hours. After the addition is completed, heat to 70-85℃ and keep the reaction at this temperature for 8-12 hours. After the reaction is completed, cool the reaction solution to 25-30℃ and slowly dropwise add a mixture of deionized water and methanol with a volume ratio of 9:1 (8-10 times the volume of the reaction solution) under vigorous stirring. Collect the solid precipitate by filtration and extract the precipitate with anhydrous ethanol using Soxhlet extraction for 18-24 hours. Then place the product in a vacuum drying oven and vacuum dry at 50-60℃ for 24-36 hours to obtain the supramolecular crosslinking agent.

[0019] The supramolecular crosslinking agent constructs an asymmetric topological structure of "rigid core-flexible UPy arms". A rigid diamine (p-phenylenediamine or 4,4'-diaminodiphenylmethane) forms the hard core, and the amino groups of the rigid diamine are bonded to the isocyanate groups of the isocyanate monomer UPy-NCO via urea bonds, connecting the long arms of UPy to both ends of the core. This crosslinking agent acts as a "supernode" in the system; it does not participate in covalent crosslinking but instead undergoes quadruple hydrogen bond dimerization with the scattered UPy groups introduced by the isocyanate monomers through its two UPy arms. This multi-point strong association weaves the originally isolated "filler-matrix" covalent bonding points into a macroscopic three-dimensional supramolecular network. The steric hindrance introduced by the IPDI framework moderately weakens the quadruple hydrogen bond association of UPy, which helps to regulate its dynamic response behavior in the melt.

[0020]

[0021] Preferably, in step (1), the molar equivalents of 2-amino-4-hydroxy-6-methylpyrimidine, isophorone diisocyanate, and dibutyltin dilaurate are 1:1:0.05.

[0022] Preferably, in step (2), the molar ratio of the rigid diamine monomer to the isocyanate monomer is 0.45-0.49:1; the rigid diamine monomer is p-phenylenediamine or 4,4'-diaminodiphenylmethane.

[0023] Preferably, the number average molecular weight of the hydroxyl-terminated polyethylene glycol is 2000 or 4000; the aromatic boric acid compound is 1,4-phenyldiboronic acid or benzene-1,3,5-trimethyltriboronic acid.

[0024] Dihydroxyl-terminated polyethylene glycol undergoes a borate esterification reaction with aromatic borate compounds, resulting in the removal of water molecules and the formation of dynamic covalent bonds in the borate ester. This reaction proceeds at a moderate rate within the temperature range of 110-130°C, and the borate ester bonds remain structurally stable below 150°C, preventing network dissociation during spinning. By strictly controlling the molar ratio of borate groups to hydroxyl groups at 0.12-1.8:1, a moderately cross-linked borate ester network is constructed.

[0025] Preferably, the maleic anhydride grafting rate of the maleic anhydride copolymer SEBS-g-MA is 1.4-2.0 wt%.

[0026] Preferably, the nano-thermal conductive filler is a carboxylated multi-walled carbon nanotube and a hydroxylated boron nitride nanosheet, with a mass ratio of 1:9 to 9:1; the carboxyl content of the carboxylated multi-walled carbon nanotube is 0.73-2.56 wt%; the hydroxyl content of the hydroxylated boron nitride nanosheet is 1.0-5.0 wt%; and the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a 1:1 mass ratio.

[0027] The polar groups on the surfaces of carboxylated carbon nanotubes and hydroxylated boron nitride have a dual function: firstly, they serve as reaction anchors for covalent bridging with isocyanate monomers; secondly, they break the original van der Waals agglomeration of the filler through hydrogen bonding, achieving nanoscale pre-dispersion. One-dimensional carbon nanotubes and two-dimensional boron nitride spontaneously form a three-dimensional thermally conductive topology of "point-to-surface contact" in the melt, significantly reducing thermal resistance. The functional group density on the filler surface is precisely controlled, ensuring sufficient bridging and grafting rates while avoiding the disruption of the intrinsic phonon heat transfer mechanism of the nanomaterials by excessive oxidation modification.

[0028] A method for preparing phase change temperature-regulating fibers includes the following steps:

[0029] Step 1: Raw material pretreatment: Place the hydroxyl-terminated polyethylene glycol, maleic anhydride copolymer SEBS-g-MA, aromatic boric acid compounds, nano-thermal conductive fillers and composite antioxidants in a vacuum drying oven and vacuum dry at 60-80℃ for 10-24 hours to remove moisture;

[0030] Step 2: Melt premixing and in-situ ring opening of acid anhydride: Add the dried bihydroxyl-terminated polyethylene glycol, maleic anhydride copolymer SEBS-g-MA, aromatic boric acid compounds, nano thermally conductive fillers and composite antioxidants to a mixer or twin-screw extruder and melt-blend at 110-130℃ for 5-15 minutes.

[0031] During the melt blending stage at 110-130℃, the maleic anhydride ring on the SEBS-g-MA chain undergoes in-situ ring-opening under the influence of heat and trace amounts of moisture, generating highly reactive carboxyl and hydroxyl groups, laying the foundation for subsequent bridging reactions. Simultaneously, the terminal hydroxyl groups of PEG begin preliminary boronic acid esterification with aromatic boric acid compounds. Due to the extremely short time, only oligomers or linear boric acid esters are formed, maintaining good fluidity and free hydroxyl groups in the system, thus preventing premature gelation.

[0032] Step 3: Dynamic grafting and supramolecular network construction: Lower the temperature to 90-110℃, add isocyanate monomer and supramolecular crosslinking agent to the reaction system, and continue mixing and reacting for 3-8 minutes to obtain a blended melt;

[0033] This stage is the core of the dual-network construction. Cooling to 90-110℃ aims to precisely control the addition reaction rate of -NCO and hydroxyl groups, preventing localized explosive polymerization. The isocyanate monomer rapidly "grabs" the pre-dispersed filler, SEBS ring-opening hydroxyl groups, and PEG terminal hydroxyl groups in the system, completing chemical anchoring and laying the foundation. Subsequently added supramolecular crosslinking agent, with its UPy arms at both ends immediately undergoing quadruple hydrogen bond dimerization with the UPy hubs at the anchoring points, weaving a physical entanglement network. In the high-shear region of the screw, the UPy hydrogen bonds instantly dissociate and absorb energy (shear thinning), giving the melt extremely low processing viscosity; upon leaving the shear region, the hydrogen bonds rapidly and reversibly recombine (structural recovery), providing melt strength. This "slip crosslinking point" mechanism completely solves the industry pain point that highly filled systems cannot be spun.

[0034] Step 4: Melt spinning and network locking: The blended melt obtained in step 3 is transferred to the spinning box, and the spinning temperature is controlled at 110-130℃. The nascent fiber is extruded through the spinneret to form a nascent fiber. After cooling and stretching, the nascent fiber is naturally cooled and shaped to obtain phase change temperature-regulating fiber.

[0035] The spinning temperature is precisely set within a safe window above the PEG melting point and below the borate ester dissociation temperature. As the melt passes through the spinneret's micropores, it undergoes intense shearing, causing the UPy supramolecular network to completely disintegrate into a fluid state. After extrusion into filaments, the shear force disappears, and the UPy network rapidly reconstructs, restoring a rubber-like state and endowing the nascent fibers with self-supporting capabilities. During subsequent drawing, the PEG segments exhibit high axial orientation, further enhancing crystallinity. Upon final cooling and setting, an interpenetrating dual-network structure is formed, consisting of a rigid borate ester covalent network that inhibits phase change material migration and leakage, and a flexible UPy supramolecular network that dissipates micro-stress, effectively locking in the phase change material and achieving zero leakage.

[0036] Application of a phase change temperature-regulating fiber in thermal insulation fabrics.

[0037] Compared with the prior art, the beneficial effects of the present invention are:

[0038] 1. This invention uses isocyanate monomers to covalently link maleic anhydride copolymer SEBS-g-MA with nano-thermal conductive fillers to form an SEBS-UPy-filler bridging structure. This structure firmly anchors the filler to the elastomer matrix, avoiding the filler agglomeration and interfacial debonding problems that easily occur in physical blending. At the same time, the UPy units can serve as binding nodes for subsequent supramolecular networks, realizing the integrated construction of filler dispersion, interfacial reinforcement, and supramolecular functions.

[0039] 2. This invention introduces a prepared supramolecular crosslinking agent into the system. The UPy units at both ends of this agent can form quadruple hydrogen bonds with the UPy nodes on the side chains of the maleic anhydride copolymer SEBS-g-MA, weaving scattered covalent anchor points into a continuous three-dimensional supramolecular network. This network can reversibly deconstruct under high-shear processing conditions, effectively reducing melt viscosity and solving the problem of unstable melt spinning in highly filled phase change systems. Under static conditions, it can rapidly reconstruct, providing the fiber with sufficient melt strength and leak-proof capability.

[0040] 3. This invention utilizes the in-situ formation of a dynamic covalent network of borate esters from hydroxyl-terminated polyethylene glycol and aromatic boric acid compounds. This network maintains structural stability within the spinning temperature range and undergoes reversible breakage and recombination with temperature changes during fiber use. This design restricts the macroscopic flow of polyethylene glycol in its molten state without significantly affecting its crystallinity, thus solving the problem of a significant decrease in latent heat of phase transition caused by traditional chemical crosslinking.

[0041] 4. This invention combines a borate ester dynamic covalent network and a UPy supramolecular network within the same fiber system, forming an interpenetrating and complementary dual dynamic structure. The borate ester network provides stable covalent constraints at high temperatures, while the UPy network provides shear-adaptive rheological behavior during processing and physical entanglement and liquid-locking properties during use. The synergistic effect of these dual dynamic networks enables the fiber to simultaneously possess high phase change enthalpy, low permeability, excellent mechanical properties, and spinnability, overcoming the inherent contradiction between the temperature regulation and processing performance of existing phase change fibers. Attached Figure Description

[0042] Figure 1 The 1H NMR spectrum of the isocyanate monomer prepared in Example 2 of this invention;

[0043] Figure 2 The above is the 1H NMR spectrum of the supramolecular crosslinking agent prepared in Example 2 of this invention. Detailed Implementation

[0044] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with existing known technologies. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0045] Example 1: A phase change temperature-regulating fiber, comprising the following components by weight:

[0046] 50g of hydroxyl-terminated polyethylene glycol, 0.5g of aromatic boric acid compound, 1g of supramolecular crosslinking agent, 10g of maleic anhydride copolymer SEBS-g-MA, 0.1g of nano-thermal conductive filler, 0.2g of composite antioxidant, and 0.5g of isocyanate monomer;

[0047] The method for preparing the isocyanate monomer and supramolecular crosslinking agent includes the following steps:

[0048] (1) Preparation of isocyanate monomer: Under nitrogen protection, 22.23 g of isophorone diisocyanate and anhydrous DMF were added to the reactor, along with 3.16 g of dibutyltin dilaurate and 0.022 g of BHT polymerization inhibitor accounting for 0.1% of the mass of isophorone diisocyanate; the molar equivalents of 2-amino-4-hydroxy-6-methylpyrimidine, isophorone diisocyanate, and dibutyltin dilaurate were 1:1:0.05; 12.51 g of 2-amino-4-hydroxy-6-methylpyrimidine was dispersed in anhydrous DMF and slowly added dropwise to the reaction solution at 0°C in an ice bath; after the addition was complete, the reaction was maintained at 0°C for 1 h, and then the temperature was raised to 40°C for 4 h. After the reaction was completed, the solvent was removed to obtain the isocyanate monomer.

[0049] (2) Preparation of supramolecular crosslinking agent: Dissolve 34.94g of isocyanate monomer obtained in step (1) in anhydrous DMF and cool to 10℃. Dissolve 4.87g of p-phenylenediamine in anhydrous DMF and control the mass percentage concentration of p-phenylenediamine to 5%. Add the mixture slowly to the reaction system under vigorous stirring for 2 hours. The molar ratio of the rigid diamine monomer to the isocyanate monomer is 0.45:1. After the addition is completed, heat to 70℃ and keep the reaction at that temperature for 8 hours. After the reaction is completed, cool the reaction solution to 25℃ and slowly add a mixture of deionized water and methanol with a volume ratio of 9:1 (8 times the volume of the reaction solution) under vigorous stirring. Collect the solid precipitate by filtration and extract the precipitate with anhydrous ethanol for 18 hours. Then place the product in a vacuum drying oven and dry it under vacuum at 50℃ for 24 hours to obtain the supramolecular crosslinking agent.

[0050] The number-average molecular weight of the hydroxyl-terminated polyethylene glycol is 2000, product number P815607, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; the aromatic boric acid compound is 1,4-phenylenediboric acid; the maleic anhydride copolymer SEBS-g-MA has a maleic anhydride grafting rate of 1.4wt%, product number FG1901, purchased from Shenzhen Wansuyuan Rubber & Plastics Co., Ltd.; the mass ratio of the carboxylated multi-walled carbon nanotubes and hydroxylated boron nitride nanosheets used as the nano-thermal conductive fillers is 1:9; the carboxyl content of the carboxylated multi-walled carbon nanotubes is 0.73wt%, product number XFM27, purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.; the hydroxyl content of the hydroxylated boron nitride nanosheets is 1.0wt%, purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.; the antioxidant is a compound of antioxidant 1010 and antioxidant 168 in a 1:1 mass ratio.

[0051] A method for preparing phase change temperature-regulating fibers includes the following steps:

[0052] Step 1: Raw material pretreatment: Place the hydroxyl-terminated polyethylene glycol, maleic anhydride copolymer SEBS-g-MA, aromatic boric acid compounds, nano-thermal conductive fillers and composite antioxidants in a vacuum drying oven and vacuum dry at 60℃ for 10 hours to remove moisture;

[0053] Step 2: Melt premixing and in-situ ring opening of acid anhydride: Add the dried bihydroxyl-terminated polyethylene glycol, maleic anhydride copolymer SEBS-g-MA, aromatic boric acid compounds, nano thermally conductive fillers and composite antioxidants into the internal mixer and melt-mix at 110°C for 5 min.

[0054] Step 3: Dynamic grafting and supramolecular network construction: Lower the temperature to 90℃, add isocyanate monomer and supramolecular crosslinking agent to the reaction system, and continue mixing and reacting for 3 minutes to obtain a blended melt;

[0055] Step 4: Melt spinning and network locking: The blended melt obtained in step 3 is transferred to the spinning box, and the spinning temperature is controlled at 110°C. The nascent fiber is extruded through the spinneret to form a nascent fiber. After cooling and stretching, the nascent fiber is naturally cooled and shaped to obtain phase change temperature-regulating fiber.

[0056] Example 2: A phase change temperature-regulating fiber, comprising the following components by weight:

[0057] 60g of hydroxyl-terminated polyethylene glycol, 1.5g of aromatic boric acid compound, 2g of supramolecular crosslinking agent, 20g of maleic anhydride copolymer SEBS-g-MA, 2.5g of nano-thermal conductive filler, 0.8g of composite antioxidant, and 1.5g of isocyanate monomer;

[0058] The method for preparing the isocyanate monomer and supramolecular crosslinking agent includes the following steps:

[0059] (1) Preparation of isocyanate monomer: Under nitrogen protection, 22.23 g of isophorone diisocyanate and anhydrous DMF were added to the reactor, along with 3.16 g of dibutyltin dilaurate and 0.022 g of BHT polymerization inhibitor (0.1% of the mass of isophorone diisocyanate). The molar equivalents of 2-amino-4-hydroxy-6-methylpyrimidine, isophorone diisocyanate, and dibutyltin dilaurate were 1:1:0.05. 12.51 g of 2-amino-4-hydroxy-6-methylpyrimidine was dispersed in anhydrous DMF and slowly added dropwise to the reaction solution at 2°C in an ice bath. After the addition was complete, the reaction was maintained at 2°C for 1.5 h, followed by a reaction at 45°C for 5 h. After the reaction was completed, the solvent was removed to obtain the isocyanate monomer. A portion of the isocyanate monomer was subjected to 1H NMR spectroscopy, and the results were as follows. Figure 1The analysis is as follows: The characteristic peak in the low-field region δ5.79–6.38 corresponds to the unsaturated hydrogen on the UPy pyrimidine ring, and the broad singlet at δ5.96 is attributed to the NH proton of the urea bond. The singlet at δ2.03 is the characteristic signal of the methyl hydrogen at position 6 on the pyrimidine ring. The multiplets in the range of δ3.05–4.23 are attributed to the methylene and methine hydrogens attached to nitrogen or oxygen atoms on the IPDI alicyclic ring. The multiplets and singlets in the range of δ0.98–1.97 correspond to the methylene hydrogen and three angular methyl hydrogens on the IPDI alicyclic skeleton, with the three singlets at δ0.98, δ1.06, and δ1.12 being the proton signals of the three methyl groups on the IPDI ring, respectively. These data indicate that the obtained product is the target isocyanate monomer, the UPy unit was successfully introduced into the structure, and the isocyanate group was effectively retained without significant side reactions, verifying the correctness of the compound structure.

[0060] (2) Preparation of supramolecular crosslinking agent: Dissolve 34.94g of isocyanate monomer obtained in step (1) in anhydrous DMF and cool to 12℃. Dissolve 9.3g of 4,4'-diaminodiphenylmethane in anhydrous DMF and control the mass percentage concentration of 4,4'-diaminodiphenylmethane to be 8%. Add the mixture slowly to the reaction system under vigorous stirring for 3h. The molar ratio of 4,4'-diaminodiphenylmethane to isocyanate monomer is 0.47:1. After the addition is completed, heat to 80℃ and keep the reaction at that temperature for 10h. After the reaction is completed, cool the reaction solution to 28℃ and slowly add a mixture of deionized water and methanol with a volume ratio of 9:1 (9 times the volume of the reaction solution) under vigorous stirring. Collect the solid precipitate by filtration and extract the precipitate with anhydrous ethanol for 20h. Then place the product in a vacuum drying oven and dry it under vacuum at 55℃ for 30h to obtain the supramolecular crosslinking agent. A portion of the supramolecular crosslinking agent was analyzed by 1H NMR spectroscopy, and the results are as follows: Figure 2 As shown: The analysis is as follows: The two singlets at δ7.79 and δ7.65 in the low-field region are attributed to the NH protons connected to the pyrimidine ring in the UPy unit; the singlet at δ6.30 is the characteristic signal of the unsaturated hydrogen at the C5 position of the UPy pyrimidine ring; and the doublet at δ2.08 is the methyl hydrogen at the 6-position of the UPy pyrimidine ring. The two sets of doublets at δ7.53 and δ7.12 are the AA'BB' spin system signals of aromatic hydrogens on the biphenyl mesocrystalline nucleus; and the singlet at δ3.84 is attributed to the methylene hydrogen connected to the rigid diamine. The multiplets at δ5.73, δ5.41, and δ4.83 are attributed to the methylene hydrogen adjacent to the urea bond on the IPDI backbone. The complex multiple peaks in the ranges of δ3.41, δ3.16, and δ1.80–0.92 correspond to the methylene hydrogen and angular methyl hydrogen on the IPDI alicyclic backbone. The characteristic signals at δ0.99 and δ0.92 are attributed to the protons of the methyl groups on the IPDI ring, which confirms that the product is the target supramolecular crosslinking agent with UPy end caps.

[0061] The number-average molecular weight of the hydroxyl-terminated polyethylene glycol is 4000, product number P815608, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; the aromatic boric acid compound is benzene-1,3,5-trimethyltriboronic acid; the maleic anhydride copolymer SEBS-g-MA has a maleic anhydride grafting rate of 1.7wt%, product number FG1901, purchased from Shenzhen Wansuyuan Rubber & Plastics Co., Ltd.; the nano-thermal conductive filler is carboxylated multi-walled carbon nanotubes and hydroxylated boron nitride nanosheets in a mass ratio of 1:1; the carboxyl content of the carboxylated multi-walled carbon nanotubes is 2.0wt%, product number XFM15, purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.; the hydroxyl content of the hydroxylated boron nitride nanosheets is 3.0wt%, purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.; the antioxidant is a compound of antioxidant 1010 and antioxidant 168 in a 1:1 mass ratio.

[0062] A method for preparing phase change temperature-regulating fibers includes the following steps:

[0063] Step 1: Raw material pretreatment: Place the hydroxyl-terminated polyethylene glycol, maleic anhydride copolymer SEBS-g-MA, aromatic boric acid compounds, nano-thermal conductive fillers and composite antioxidants in a vacuum drying oven and vacuum dry at 70°C for 20 hours to remove moisture;

[0064] Step 2: Melt premixing and in-situ ring opening of acid anhydride: The dried bihydroxyl-terminated polyethylene glycol, maleic anhydride copolymer SEBS-g-MA, aromatic boric acid compounds, nano thermally conductive fillers and composite antioxidants are added to a twin-screw extruder and melt-blended at 120°C for 10 min.

[0065] Step 3: Dynamic grafting and supramolecular network construction: Lower the temperature to 100℃, add isocyanate monomer and supramolecular crosslinking agent to the reaction system, and continue mixing and reacting for 6 minutes to obtain a blended melt;

[0066] Step 4: Melt spinning and network locking: The blended melt obtained in step 3 is transferred to the spinning box, the spinning temperature is controlled at 120℃, and the nascent fiber is formed by extrusion through the spinneret; after cooling and stretching, the nascent fiber is naturally cooled and shaped to obtain phase change temperature-regulating fiber.

[0067] Example 3: A phase change temperature-regulating fiber, comprising the following components by weight:

[0068] 80g of hydroxyl-terminated polyethylene glycol, 5g of aromatic boric acid compound, 5g of supramolecular crosslinking agent, 40g of maleic anhydride copolymer SEBS-g-MA, 5g of nano-thermal conductive filler, 1.0g of composite antioxidant, and 3g of isocyanate monomer;

[0069] The method for preparing the isocyanate monomer and supramolecular crosslinking agent includes the following steps:

[0070] (1) Preparation of isocyanate monomer: Under nitrogen protection, 22.23 g of isophorone diisocyanate and anhydrous DMF were added to the reactor, along with 3.16 g of dibutyltin dilaurate and 0.022 g of BHT polymerization inhibitor accounting for 0.1% of the mass of isophorone diisocyanate; the molar equivalents of 2-amino-4-hydroxy-6-methylpyrimidine, isophorone diisocyanate, and dibutyltin dilaurate were 1:1:0.05; 12.51 g of 2-amino-4-hydroxy-6-methylpyrimidine was dispersed in anhydrous DMF and slowly added dropwise to the reaction solution at 5°C in an ice bath; after the addition was complete, the reaction was maintained at 10°C for 2 h, and then the temperature was raised to 50°C for 6 h. After the reaction was completed, the solvent was removed to obtain the isocyanate monomer;

[0071] (2) Preparation of supramolecular crosslinking agent: Dissolve 34.94g of isocyanate monomer obtained in step (1) in anhydrous DMF and cool to 15°C. Dissolve 5.30g of p-phenylenediamine in anhydrous DMF and control the mass percentage concentration of p-phenylenediamine to 10%. Add the mixture slowly to the reaction system under vigorous stirring for 4 hours. The molar ratio of the rigid diamine monomer to the isocyanate monomer is 0.49:1. After the addition is completed, heat the mixture to 85°C and keep it at that temperature for 12 hours. After the reaction is completed, cool the reaction solution to 30°C and add a mixture of deionized water and methanol with a volume ratio of 9:1 (10 times the volume of the reaction solution) slowly under vigorous stirring. Collect the solid precipitate by filtration and extract the precipitate with anhydrous ethanol for 24 hours. Then place the product in a vacuum drying oven and dry it under vacuum at 60°C for 36 hours to obtain the supramolecular crosslinking agent.

[0072] The bihydroxyl-terminated polyethylene glycol has a number average molecular weight of 4000, product number P815608, and was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; the aromatic boronic acid compound is benzene-1,3,5-trimethyltriboronic acid; the maleic anhydride copolymer SEBS-g-MA has a maleic anhydride grafting rate of 2.0 wt%, product number FG1901, and was purchased from Shenzhen Wansuyuan Rubber & Plastics Co., Ltd.; the nano-thermal conductive filler is carboxylated multi-walled carbon nanotubes and hydroxylated boron nitride nanosheets in a mass ratio of 9:1; the carboxyl content of the carboxylated multi-walled carbon nanotubes is 2.56 wt%, product number XFM09, and was purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.; the hydroxyl content of the hydroxylated boron nitride nanosheets is 5.0 wt%, and was purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.; the antioxidant is a compound of antioxidant 1010 and antioxidant 168 in a 1:1 mass ratio.

[0073] A method for preparing phase change temperature-regulating fibers includes the following steps:

[0074] Step 1: Raw material pretreatment: Place the hydroxyl-terminated polyethylene glycol, maleic anhydride copolymer SEBS-g-MA, aromatic boric acid compounds, nano-thermal conductive fillers and composite antioxidants in a vacuum drying oven and vacuum dry at 80℃ for 24 hours to remove moisture;

[0075] Step 2: Melt premixing and in-situ ring opening of acid anhydride: The dried bihydroxyl-terminated polyethylene glycol, maleic anhydride copolymer SEBS-g-MA, aromatic boric acid compounds, nano thermally conductive fillers and composite antioxidants are added to a twin-screw extruder and melt-blended at 130°C for 15 min.

[0076] Step 3: Dynamic grafting and supramolecular network construction: Lower the temperature to 110℃, add isocyanate monomer and supramolecular crosslinking agent to the reaction system, and continue mixing and reacting for 8 minutes to obtain a blended melt;

[0077] Step 4: Melt spinning and network locking: The blended melt obtained in step 3 is transferred to the spinning box, the spinning temperature is controlled at 130℃, and the nascent fiber is formed by extrusion through the spinneret; after cooling and stretching, the nascent fiber is naturally cooled and shaped to obtain phase change temperature-regulating fiber.

[0078] Comparative Example 1: Based on Example 2, without the addition of a supramolecular crosslinking agent, the rest is the same as Example 2.

[0079] Comparative Example 2: Based on Example 2, no isocyanate monomer was added, and no chemical bridging structure was formed between the maleic anhydride copolymer SEBS-g-MA and the nano-thermal conductive filler. The rest was the same as in Example 2.

[0080] Comparative Example 3: Based on Example 2, without adding the aromatic boric acid compound benzene-1,3,5-trimethyltriboronic acid, without constructing a dynamic covalent network of borate esters, the rest is the same as Example 2.

[0081] Comparative Example 4: Based on Example 2, unmodified multi-walled carbon nanotubes and unmodified boron nitride nanosheets were used, but carboxylated and hydroxylated functionalized nano-thermal conductive fillers were not used. The rest was the same as in Example 2.

[0082] Comparative Example 5: Based on Example 2, the molar ratio of boric acid groups in the aromatic boric acid compound to terminal hydroxyl groups in the bihydroxyl-terminated polyethylene glycol was adjusted to 2.0:1, which exceeds the limited range of 0.12-1.8:1. The rest is the same as in Example 2.

[0083] Comparative Example 6: Based on Example 2, PEG phase change microcapsule powder was used to replace the hydroxyl-terminated polyethylene glycol. The substitution was based on the actual content of PEG in the microcapsules, so that the effective mass of PEG in the system was the same as the amount of PEG used in Example 2. Isocyanate monomers, supramolecular crosslinking agents and aromatic boric acid compounds were not added; the rest was the same as in Example 2.

[0084] Comparative Example 7: Based on Example 2, pentaerythritol was used to replace the isocyanate monomer and supramolecular crosslinking agent by mass. The hydroxyl groups of pentaerythritol reacted with the isocyanate monomer to form a static covalent crosslinking system. The rest was the same as in Example 2.

[0085] Performance testing: The phase change temperature-regulating fibers prepared in Examples 1-3 and Comparative Examples 1-7, and the fabrics obtained by applying them to fabrics, were subjected to the following performance tests. The test methods and results are as follows:

[0086] Test Example 1: Performance Testing of Phase Change Temperature Regulating Fibers

[0087] 1. Phase transition performance test: Differential scanning calorimetry was used. 8 mg of shredded fiber sample was placed in an aluminum crucible under a nitrogen atmosphere (flow rate 50 mL / min). The following procedure was used: the temperature was increased from -20℃ to 100℃ at a rate of 10℃ / min, and then decreased to -20℃ at a rate of 10℃ / min. The melting temperature, crystallization temperature, enthalpy of fusion, and enthalpy of crystallization were recorded.

[0088] 2. Mechanical property testing: Referring to GB / T14344-2022 "Test Method for Tensile Properties of Chemical Fiber Filaments", the fibers were equilibrated for 24 hours under standard atmospheric conditions (20±2℃, relative humidity 65±5%). A single-fiber strength tester was used with a clamping distance of 20mm and a tensile speed of 20mm / min. An appropriate pre-tension (calculated based on a linear density of 0.05cN / dtex) was applied to the fibers during testing, and the breaking strength and elongation at break were recorded. Twenty filaments were tested in each group, and the arithmetic mean was taken. The breakage rate at the clamping point should not exceed 10%.

[0089] 3. Thermal stability test: Thermogravimetric analysis was used for testing. 8 mg of fiber sample was taken and heated to 800℃ at a nitrogen atmosphere (flow rate 50 mL / min) at a rate of 10℃ / min. The initial decomposition temperature (5% mass loss temperature), the maximum decomposition rate temperature, and the char residue at 800℃ were recorded.

[0090] 4. Leakage Rate Test: The filter paper method was used. Approximately 0.5g of fiber sample was accurately weighed and wrapped in quantitative filter paper. The following two conditions were applied: (a) constant temperature heating at 60±2℃ for 24 hours; (b) constant temperature heating at 80±2℃ for 1 hour. After heating, the sample was removed, the fibers were separated, and the filter paper was dried to constant weight. The leakage rate was calculated as the percentage of filter paper weight gain to the mass of phase change material in the sample. Each group was tested in triplicate, and the average value was taken.

[0091] 5. Thermal Cycling Stability Test: The fiber samples were subjected to thermal cycling: 80±2℃ for 30 min, followed by 0±2℃ for 30 min, constituting one cycle. After 100 cycles, the samples were removed to observe whether the fiber morphology remained intact and whether there was any adhesion or tufting. The phase transition enthalpy and breaking strength of the samples after cycling were tested, and the enthalpy retention rate and strength retention rate were calculated. Each group was tested in triplicate, and the average value was taken.

[0092] 6. Thermal conductivity test: The transient hot wire method was used, referring to GB / T10297-2015 "Determination of thermal conductivity of non-metallic solid materials - hot wire method". Approximately 10g of fiber was pressed into uniform cylinders with a diameter of 30mm and a thickness of approximately 5mm in a special mold, controlling the fiber cylinder bulk density within the range of 0.3-0.5g / cm³. The thermal conductivity was tested at 25℃, 40℃, and 60℃ respectively, with each group tested three times and the average value taken.

[0093] 7. Spinnability Evaluation: During melt spinning, record the continuous spinning time, fiber breakage frequency, number of filaments, and coefficient of variation (CV) of fiber diameter. Evaluation criteria: "Excellent" is defined as continuous spinning time ≥ 8h, fiber breakage frequency ≤ 1 time / h, number of filaments ≤ 5 / 1000m, and diameter CV value ≤ 5%; "Good" is defined as continuous spinning time 4-8h, fiber breakage frequency 2-3 times / h, number of filaments 6-10 / 1000m, and diameter CV value 5-10%; "Poor" is defined as continuous spinning time < 4h, fiber breakage frequency ≥ 4 times / h, number of filaments ≥ 11 / 1000m, and diameter CV value ≥ 10%. Compare the evaluation results with a control sample under the same spinning equipment and linear speed conditions.

[0094] Test Example 2: Performance Testing of Fabrics: The fibers from the examples and comparative examples were knitted into double rib fabrics on an 18-gauge / inch circular knitting machine, with a weight of 200±10 g / m². 2 The yarn length is 28cm / 100 stitches, and the tensile tension is 2-3cN. The fabric is washed at 40℃ for 20 minutes and dried at 80℃ for setting, then ready for use.

[0095] 1. Fabric temperature regulation performance test: (1) DSC method: Refer to GB / T43820-2024 "Determination of heat storage and heat release properties of textiles containing phase change materials", cut the fabric into small pieces and take samples. Heat from -20℃ to 60℃ at a rate of 5℃ / min, and then cool down to -20℃ at a rate of 5℃ / min. Record the melting enthalpy of the second heating curve and the crystallization enthalpy of the cooling curve.

[0096] (2) Hot table method: Place a 5cm×5cm fabric sample on a constant temperature hot table. Set the hot table temperature to 35℃ and the ambient temperature to 20℃. Use an infrared thermal imager or thermocouple to record the change curve of the fabric surface temperature over time. The temperature adjustment effect is evaluated by the duration of the temperature plateau and the temperature difference ΔT between the sample and the blank cotton fabric sample. Each group is tested 3 times and the average value is taken.

[0097] 2. Fabric air permeability test: Refer to GB / T5453-1997, test pressure difference 100Pa, test area 20cm². 2 The airflow rate was measured and the air permeability (mm / s) was calculated. The average value was taken from 10 different locations in each group of tests.

[0098] 3. Fabric moisture permeability test: Referring to GB / T12704.1-2009, the moisture absorption method was used to test the moisture permeability at 38℃ and 90% relative humidity. The unit is g / (m²). 2 • 24h). Each group was tested 3 times and the average value was taken.

[0099] 4. Fabric thermal insulation performance test: Refer to GB / T35762-2017 "Test Method for Heat Transfer Properties of Textiles - Flat Plate Method", with a hot plate temperature of 35℃, an ambient temperature of 20℃, and a relative humidity of 65%. First, measure the thermal resistance Rct0 of the empty plate, then lay the fabric sample flat on the hot plate and measure the total thermal resistance Rct1. The sample thermal resistance Rct = Rct1 - Rct0, and the clo value = Rct / 0.155. At least 3 parallel samples should be tested in each group, and the average value should be taken.

[0100] Table 1. Fiber performance test results of examples and comparative examples

[0101] Table 2. Performance test results of fabrics from the examples and comparative examples

[0102] Data analysis: The phase change temperature-regulating fibers prepared in Examples 1-3 all exhibit high phase change enthalpy values, reaching up to 102.5 J / g, breaking strength exceeding 3.28 cN / dtex, leakage rate below 1%, and enthalpy retention rate exceeding 96% after thermal cycling, with excellent spinnability. The data from the three examples are similar, with Example 2 showing slightly better overall performance.

[0103] In Comparative Example 1, without the addition of a supramolecular crosslinking agent, the fiber's breaking strength decreased to 2.56 cN / dtex, its breaking elongation decreased to 41.2%, and its leakage rate at 60℃ increased to 1.8%, resulting in a moderate spinnability rating. This indicates that the absence of a supramolecular crosslinking agent prevents the scattered UPy units from being woven into a macroscopic three-dimensional network, leading to insufficient melt strength and a significant decrease in mechanical properties and leakage resistance.

[0104] Comparative Example 2, without the addition of isocyanate monomers, showed no chemical bridging between SEBS-g-MA and the nanofiller. The fiber exhibited a breaking strength of only 2.12 cN / dtex, and its thermal conductivity at all temperatures was lower than that of Example 2, with a moderate spinnability rating. This demonstrates that the UPy bridging structure is crucial for stable filler dispersion and interfacial reinforcement; without covalent bonding, filler agglomeration leads to simultaneous deterioration of both mechanical and thermal properties.

[0105] Comparative Example 3 did not add aromatic borate compounds and did not construct a dynamic covalent network of borate esters. Its leakage rate at 60°C was 2.1%, the leakage rate at 80°C was 4.2%, and the enthalpy retention rate after 100 cycles was 93.2%, all of which were worse than those of Example 2. This indicates that the borate ester network is the main constraint limiting PEG flow at high temperatures. Without it, the phase change material is prone to migration and leakage in the molten state, resulting in decreased thermal cycling stability.

[0106] Comparative Example 4 used unmodified multi-walled carbon nanotubes and unmodified boron nitride nanosheets, with no hydroxyl / carboxyl reaction sites on the filler surface. The thermal conductivity of this fiber at 25°C was only 0.26 W / m·K, far lower than the 0.56 W / m·K of Example 2, and the leakage rate and mechanical properties were also significantly deteriorated. This indicates that filler functionalization is a prerequisite for achieving chemical bridging; without reaction anchors, the filler cannot be anchored by the UPy network, and the dispersion effect and thermal conductivity enhancement are greatly weakened.

[0107] Comparative Example 5 adjusted the molar ratio of boric acid groups to terminal hydroxyl groups to 2.0:1, exceeding the range of 0.12 to 1.8. The phase transition enthalpy of this fiber decreased to 64.2 J / g, the elongation at break decreased to 28.5%, and the leakage rate at 80℃ increased to 8.9%. This indicates that excessively high crosslinking density severely restricts the movement of PEG molecular chains, reduces crystallinity, significantly reduces latent heat of phase transition, and the excessive network stiffness leads to decreased toughness.

[0108] Comparative Example 6 used traditional PEG microcapsule physical blending to replace the chemical anchoring system of this invention. The fiber exhibited a phase change enthalpy of only 42.5 J / g, a leakage rate as high as 12.6% at 60℃ and 28.4% at 80℃, and an enthalpy retention rate of only 68.5% after 100 cycles, resulting in poor spinnability. The data indicate that the microcapsules ruptured extensively under the high temperature and high shear of melt spinning, leading to core material leakage, near-complete loss of temperature regulation function, and inability to continuously spin.

[0109] Comparative Example 7 used pentaerythritol to replace the isocyanate monomer and supramolecular crosslinking agent in equal amounts to form a static covalent crosslinking system. The fiber's elongation at break was only 25.6%, its spinnability was rated as poor, and its leakage rate at 60°C was still 6.2%. This indicates that the static crosslinking network lacks dynamic reversibility, the melt viscosity is too high to spin, and the crosslinking points are irreversible and cannot dissipate stress, resulting in high material brittleness and a less effective anti-leakage effect compared to the dual dynamic network of this invention.

[0110] In summary, this invention achieves covalent bonding between the filler and the matrix through an UPy bridging structure, weaves a macroscopic three-dimensional supramolecular network using a supramolecular crosslinking agent, and provides high-temperature constraint through dynamic covalent bonds of borate esters. These three elements synergistically enable the fiber to simultaneously possess high phase change enthalpy, low permeability, good mechanical properties, and spinnability. Comparative Examples 1 to 7, lacking or deviating from any of the above key designs, all resulted in a significant decrease in at least one core performance characteristic, verifying the irreplaceable nature of the technical solution of this invention.

[0111] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A phase change temperature-regulating fiber, characterized in that, The raw material components include the following parts by weight: 50-80 parts of hydroxyl-terminated polyethylene glycol, 0.5-5 parts of aromatic boric acid compounds, 1-5 parts of supramolecular crosslinking agent, 10-40 parts of maleic anhydride copolymer SEBS-g-MA, 0.1-5 parts of nano-thermal conductive filler, 0.2-1.0 parts of composite antioxidant, and 0.5-3 parts of isocyanate monomer; The number-average molecular weight of the hydroxyl-terminated polyethylene glycol is 2000 or 4000. The aromatic boric acid compound is 1,4-phenyldiboronic acid or benzene-1,3,5-trimethyltriboronic acid; The molar ratio of the boric acid group in the aromatic boric acid compound to the terminal hydroxyl group in the double-terminated polyethylene glycol is 0.12-1.8:1; The supramolecular crosslinking agent is prepared by reacting an isocyanate monomer with a rigid diamine monomer; the rigid diamine monomer is p-phenylenediamine or 4,4'-diaminodiphenylmethane; the molar ratio of the rigid diamine monomer to the isocyanate monomer is 0.45-0.49:1; The maleic anhydride grafting rate of the maleic anhydride copolymer SEBS-g-MA is 1.4-2.0 wt%. The nano-thermal conductive filler is a carboxylated multi-walled carbon nanotube and a hydroxylated boron nitride nanosheet, with a mass ratio of 1:9-9:

1. The isocyanate monomer is an UPy intermediate containing a monoisocyanate group, which is prepared by reacting 2-amino-4-hydroxy-6-methylpyrimidine with isophorone diisocyanate in a molar ratio of 1:

1. The maleic anhydride copolymer SEBS-g-MA and the nano-thermal conductive filler are bridged by the isocyanate monomer; in the bridging structure, the isocyanate group of the isocyanate monomer forms a carbamate bond with the hydroxyl group generated by in-situ ring opening on the maleic anhydride copolymer SEBS-g-MA chain and the hydroxyl group on the surface of the nano-thermal conductive filler, with the UPy group as the bridging node.

2. The phase change temperature-regulating fiber according to claim 1, characterized in that, The preparation method of the isocyanate monomer and supramolecular crosslinking agent includes the following steps: (1) Preparation of isocyanate monomer: Under nitrogen protection, isophorone diisocyanate and anhydrous DMF are added to the reactor, along with dibutyltin dilaurate and BHT polymerization inhibitor at 0.1% of the mass of isophorone diisocyanate; 2-amino-4-hydroxy-6-methylpyrimidine is dispersed in anhydrous DMF and slowly added dropwise to the reaction solution at 0-5℃ in an ice bath; after the addition is complete, the reaction is maintained at 0-10℃ for 1-2 h, and then the temperature is raised to 40-50℃ for 4-6 h. After the reaction is completed, the solvent is removed to obtain the isocyanate monomer. (2) Preparation of supramolecular crosslinking agent: Dissolve the isocyanate monomer obtained in step (1) in anhydrous DMF and cool to 10-15℃. Dissolve the rigid diamine monomer in anhydrous DMF and control the mass percentage concentration of the rigid diamine monomer to be 5-10%. Add it slowly dropwise to the reaction system under vigorous stirring for 2-4 hours. After the addition is completed, heat to 70-85℃ and keep the reaction at this temperature for 8-12 hours. After the reaction is completed, cool the reaction solution to 25-30℃ and slowly dropwise add a mixture of deionized water and methanol with a volume ratio of 9:1 (8-10 times the volume of the reaction solution) under vigorous stirring. Collect the solid precipitate by filtration and extract the precipitate with anhydrous ethanol using Soxhlet extraction for 18-24 hours. Then place the product in a vacuum drying oven and vacuum dry at 50-60℃ for 24-36 hours to obtain the supramolecular crosslinking agent.

3. The phase change temperature-regulating fiber according to claim 2, characterized in that, In step (1), the molar equivalents of 2-amino-4-hydroxy-6-methylpyrimidine, isophorone diisocyanate, and dibutyltin dilaurate are 1:1:0.

05.

4. The phase change temperature-regulating fiber according to claim 1, characterized in that, The carboxylated multi-walled carbon nanotubes have a carboxyl content of 0.73-2.56 wt%; the hydroxylated boron nitride nanosheets have a hydroxyl content of 1.0-5.0 wt%; and the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a 1:1 mass ratio.

5. A method for preparing phase change temperature-regulating fibers as described in any one of claims 1-4, characterized in that, Includes the following steps: Step 1: Raw material pretreatment: Place the hydroxyl-terminated polyethylene glycol, maleic anhydride copolymer SEBS-g-MA, aromatic boric acid compounds, nano-thermal conductive fillers and composite antioxidants in a vacuum drying oven and vacuum dry at 60-80℃ for 10-24 hours to remove moisture; Step 2: Melt premixing and in-situ ring opening of acid anhydride: Add the dried bihydroxyl-terminated polyethylene glycol, maleic anhydride copolymer SEBS-g-MA, aromatic boric acid compounds, nano thermally conductive fillers and composite antioxidants to a mixer or twin-screw extruder and melt-blend at 110-130℃ for 5-15 minutes. Step 3: Dynamic grafting and supramolecular network construction: Lower the temperature to 90-110℃, add isocyanate monomer and supramolecular crosslinking agent to the reaction system, and continue mixing and reacting for 3-8 minutes to obtain a blended melt; Step 4: Melt spinning and network locking: The blended melt obtained in step 3 is transferred to the spinning box, and the spinning temperature is controlled at 110-130℃. The nascent fiber is extruded through the spinneret to form a nascent fiber. After cooling and stretching, the nascent fiber is naturally cooled and shaped to obtain phase change temperature-regulating fiber.

6. The application of the phase change temperature-regulating fiber as described in any one of claims 1-4 in thermal insulation fabrics.

Citation Information

Patent Citations

  • Preparation method of temperature-adjustable polyurethane composite phase change fiber

    CN114574998A

  • Bombax cotton phase-change material production method

    CN1936169A